Precision Mushroom Farm Monitoring System With Classification of Toxic Mushrooms in Punjab : A Comprehensive Review - Singh, Navdeep; Singh, Joga (Indian Journal of Computer Science, 2024)
The present paper presents research findings and research gaps relating to the use of research and development in mushroom cultivation based agriculture. This in-depth analysis delves into the significant effects of incorporating cutting-edge technologies into mushroom cultivation. It focuses on creating a precise monitoring and control system customized for growing mushrooms, as well as using advanced methods to detect harmful mushroom varieties. Furthermore, the analysis looks into potential impacts on agricultural efficiency, food safety, and preventive healthcare, underscoring broader societal effects. This synthesis strives to provide a comprehensive insight into how precision farming, IoT, and Machine learning collaborate to build a strong ecosystem for secure and efficient mushroom farming. It concludes by advocating for a well-rounded approach that tackles security, scalability, and ethical considerations when implementing such systems, fostering sustainable, and safe progress in precision mushroom cultivation.